IMPLEMENTASI ALAT PERAGA OPERASI BILANGAN BULAT BAGI GURU SEKOLAH DASAR (SD) SE-KECAMATAN ILIR BARAT I PALEMBANG - Ratu Ilma (Jurnal Pendidikan Matematika, 2011)
The purpose of this activity is to increase the ability of teachers in 1) make mathematics manipulative Â as a media of operations of Â integer, 2) used mathematics manipulative is made in classroom simulation. Method of the activities performed is a demonstration, presentations and discussion. The participants of this activity are 25 teachers of â€œKecamatan Ilir Barat I" Palembang. The results of the activities showed that, 95% of teachers are involved in each mathematics activities, discussions, and simulations. The results of pre test and post test showed that there is increasing ability of mathematics teachers in â€œKecamatan Ilir Barat Iâ€ Palembang. The results of questionnaire showed that 100% of participants felt very satisfied follow the given activities and want the existence of a follow-up activity. Â  Keywords: Operation of integer, Mathematics Manipulative, MediaÂ